Pengaruh Keputusan Investasi, Profitabilitas Dan Tax Avoidance Terhadap Nilai Perusahaan - Triana; Hotang, Keri Boru; Nur Fatimah, Anisa Putri (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2022)
The purpose of this research is to obtained evidence about the impact of independent variables that consisting of investment decisions, profitability and tax avoidance on the dependent variable of firm value. The companies used in this study are LQ 45 companies listed on the Indonesia Stock Exchange (BEI) from 2016-2019 with criteria using the purposive sampling method. This research uses IBM SPSS version 24 software. The results showed that simultaneously, the investment decision variable, profitability and tax avoidance had a significant effect on firm value. The tax avoidance variable partially has no effect on firm value. Meanwhile, the investment decision and profitability variables partially indicate a positive and significant influence on firm value.